2011
DOI: 10.1016/j.jare.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Zinc phosphide toxicity with a trial of tranexamic acid in its management

Abstract: Zinc phosphide is a highly effective rodenticide used widely to protect grain in stores and domestically to kill rodents. Acute poisoning may be direct by ingestion or indirect through accidental inhalation of phosphine gas generated during its use. This study aims to identify the patterns of intoxication with zinc phosphide among Egyptian patients admitted to the National Egyptian Center of Clinical and Environmental Toxicological Research (NECTR); to study the role of antifibrinolytics in management of zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…The mean age of studied patients was 24.67±11.29 years. This is in accordance with several studies reported that acute phosphide poisoning was common in young adults (El Naggar and El Mahdy., 2011;Soltaninejad et al, 2012 andElghany et al, 2018).This was explained by exposure of this age group to unemployment and financial instability (Chandrakant et al, 2015;Dadpour et al, 2016). On the other hand, a study in India by Gupta et al (2011) found that accidental ALP ingestion was common in children due to illiteracy and its easy availability in the Indian agricultural community.…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of studied patients was 24.67±11.29 years. This is in accordance with several studies reported that acute phosphide poisoning was common in young adults (El Naggar and El Mahdy., 2011;Soltaninejad et al, 2012 andElghany et al, 2018).This was explained by exposure of this age group to unemployment and financial instability (Chandrakant et al, 2015;Dadpour et al, 2016). On the other hand, a study in India by Gupta et al (2011) found that accidental ALP ingestion was common in children due to illiteracy and its easy availability in the Indian agricultural community.…”
Section: Discussionsupporting
confidence: 93%
“…Acute phosphide poisoning (zinc or aluminum) produced PH 3 within 30 min of ingestion in the body, which is extremely toxic and highly irritating to the respiratory tract and also caused severe systemic toxicity. Death may result in less than 6 h due to pulmonary edema, cardiotoxicity, refractory hypotension, cardiogenic shock, and multiorgan failure [13,14]. Occasionally, there may be a delay in the onset of symptoms by 3 days and therefore, it is suggested that the patient should be placed under observation for at least 72 h after the ingestion of phosphine containing products.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Due to its low price and easy availability, phosphide is emerging as a common self-poisoning agent in Egypt. (2) Reported morbidity and mortality rate due to phosphide poisoning is too high, especially in developing countries and in Egypt. (2,3) Acute poisoning with zinc phosphides may occur either through direct ingestion of the salts themselves or indirect inhalation of the phosphine gas generated on exposure to moisture.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Reported morbidity and mortality rate due to phosphide poisoning is too high, especially in developing countries and in Egypt. (2,3) Acute poisoning with zinc phosphides may occur either through direct ingestion of the salts themselves or indirect inhalation of the phosphine gas generated on exposure to moisture. (1) When zinc phosphide comes in contact with water, moisture in the air, or hydrochloric acid in the stomach, a chemical reaction starts releasing phosphine gas which is rapidly absorbed throughout the gastrointestinal tract and the lungs.…”
Section: Introductionmentioning
confidence: 99%